Double Dielectric Barrier (DBD) plasma-assisted deposition of chemical stabilized nanoparticles on polyamide 6,6 and polyester fabrics - Ribeiro, Ana (2017)
The development of new multifunctional textiles containing nanoparticles (NPs) has had a special interest in several applications for pharmaceutical, medical, engineering, agricultural, and food products.[1-2] Cu, Zn and especially Ag NPs exhibit strong antibacterial activities on a broad spectrum of bacteria.[3-5] Most of the antimicrobial textiles coated with NPs are not able to perform a controlled release of the antibiotic species. Thus, the immobilization of NPs in the substrate or its inclusion in polymeric matrix is essential to control the NPs antibiotic effect with time. Dielectric barrier discharge (DBD) plasma technology is one of the most effective non-thermal plasma sources.[6] However, an even dispersion and coating of NPs onto fabrics remain a challenge due to the high degree of aggregation of metal NPs.[7] Some capping agents were described to increase the suspension stability such as citrate and SDS.[8] In this work, Ag, Zn, and Cu NPs deposition on DBD plasma pre-treated polyamide 6,6 (PA66) and polyester (PES) were tested for the production of durable antibacterial textiles. SEM-EDX analysis and the effect of some NPs stabilizers (e.g. sodium citrate, sodium alginate and Polyvinyl alcohol (PVA)) was analysed by dynamic light scattering (DLS) in term of size, polydispersity index and zeta potential. XPS analyses prove the DBD efficacy in providing oxygen species onto the fabric’s surfaces. The SEM analyses prove the deposition of the Ag and Cu NPs onto the PES and PA66 fabrics. No zinc was detected. However, antimicrobial tests in PES shows that all the NPs have an antimicrobial effect but Cu and Zn show activity only in S. aureus and Ag only in E.coli. Cu shows a reasonable dispersion onto the fibres but PVP coated AgNPs display a high level of aggregation even after 1 hour of ultrasonic treatment. To solve instability and aggregation problems, NPs suspensions were prepared in different concentrations (1, 2.5 and 5 wt%) of citrate, alginate and PVA using water and ethanol as control by ultrasonic bath. In table 1 are resumed the best results obtained for each NP compared to water as control. Ethanol and PVA were disregarded due to the highest instability and lowest ζ potential, respectively. XPS, SEM and antimicrobial data shows lack in coating uniformity. It is clear that doesn't exist a univocal dispersant and concentration for all NPs. Despite the improving in ζ potentials and stability of the colloids, the obtained sizes still show a high degree of aggregation.